Treatment of osteoarthritis: A focus on nimesulide - G. R. Imametdinova; N. V. Chichasova (Современная ревматология)
Widespread osteoarthritis (OA) and high related disability rates determine not only the medical, but also socioeconomic significance of this disease. In recent years there has been a tendency to increase the incidence of OA. According to the current concepts, inflammation plays a leading role in the development of chronic pain in OA, which requires adequate anti-inflammatory therapy. There are data on the diverse mechanisms of action of the nonsteroidal anti-inflammatory drug (NSAID) nimesulide and results from clinical trials and metaanalyses, which confirm its efficacy and good tolerability. Several clinical trials covering 22,938 patients with OA have indicated that the overall frequency of adverse reactions (AR) from nimesulide is 8.2%. There is evidence on the efficacy and good tolerability of topical NSAIDs, as well as combination drugs containing glucosamine sulfate and chondroitin sulfate, the use of which together with oral drugs enhances the efficiency of treatment without increasing the risk of ARs.